2013
DOI: 10.1111/1574-6941.12081
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbial communities of healthy adult dogs fed raw meat-based diets with or without inulin or yeast cell wall extracts as assessed by 454 pyrosequencing

Abstract: Our objective was to determine the effects of feeding raw meat-based diets with or without inulin or yeast cell wall extract (YCW) on fecal microbial communities of dogs using 454 pyrosequencing. Six healthy female adult beagles (5.5 ± 0.5 years; 8.5 ± 0.5 kg) were randomly assigned to six test diets using a Latin square design: (1) beef control; (2) beef + 1.4% inulin; (3) beef + 1.4% YCW; (4) chicken control; (5) chicken + 1.4% inulin; and (6) chicken + 1.4% YCW. Following 14 days of adaptation, fresh fecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 57 publications
9
105
0
6
Order By: Relevance
“…However, the phyla Spirochaetes, Tenericutes, Verruco-microbia, Cyanobacteria and Chloroflexi have also been identified. In the study by Beloshapka et al (2013), predominant bacterial families in adult beagles fed raw meat-based diets included Fusobacteriaceae, Clostridiaceae, and Bacteroidaceae and predominant genera included Fusobacterium, Cetobacterium, Clostridium, and Bacteroides. Moreover, the canine intestine also hosts nonbacterial microorganisms.…”
Section: The Intestinal Microbiota Of Dogsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the phyla Spirochaetes, Tenericutes, Verruco-microbia, Cyanobacteria and Chloroflexi have also been identified. In the study by Beloshapka et al (2013), predominant bacterial families in adult beagles fed raw meat-based diets included Fusobacteriaceae, Clostridiaceae, and Bacteroidaceae and predominant genera included Fusobacterium, Cetobacterium, Clostridium, and Bacteroides. Moreover, the canine intestine also hosts nonbacterial microorganisms.…”
Section: The Intestinal Microbiota Of Dogsmentioning
confidence: 99%
“…Thanks to more recent studies making use of molecular identification methods (Suchodolski et al, 2009;Middelbos et al, 2010;Handl et al, 2011;Suchodolski, 2011;Swanson et al, 2011;Beloshapka et al, 2013), hundreds of phylotypes have been identified in the intestine of the dog. The phyla Firmicutes, Bacteroidetes, Proteobacteria, Fusobacteria and Actinobacteria account for over 99% of the bacterial species harboured in the intestine of dogs.…”
Section: The Intestinal Microbiota Of Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular approaches, such as 16S ribosomal RNA (rRNA) clone libraries (Eichler et al 2006;Gihring et al 2012;Zhang et al 2013a) and polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) (Garrido et al 2014;González-Arenzana et al 2013;Sun et al 2013;Zhang et al 2013b), have greatly increased our comprehension of microbial communities, although these methods poorly represent the rare bacterial groups. In recent years, 454 pyrosequencing has been introduced as a next-generation sequencing method for revealing relatively detailed profiles of microbial communities (Beloshapka et al 2013;Jackson et al 2012). The main advantages of 454 pyrosequencing are a much lower cost per base, the omission of a plasmid cloning step, a large amount of sequence data per run, and long read lengths with an average of up to 400 bps (Glenn 2011;Margulies et al 2005).…”
mentioning
confidence: 99%
“…Middelbos et al [6] investigated the fecal bacterial communities of dogs fed diets with or without dietary fiber, whereas Garcia-Mazcorro et al [7] investigated the fecal bacterial communities of dogs fed diets with or without synbiotics. Beloshapka et al [8] used next-generation pyrosequencing to examine the effect of inulin or yeast cell wall extracts on the fecal bacterial communities of dogs. These three studies showed that diet greatly affected the fecal bacterial communities of dogs.…”
Section: Introductionmentioning
confidence: 99%